SCREENING OF THE ACID MEAT CONDITION IN THE RENDEMENT NAPOLE GENE USING POLYMERASE CHAIN REACTION - RESTRICTION FRAGMENT LENGTH POLYMORPHISM - Claro Niegos Mingala; Jessica G. Manalaysay; Nathaniel D. Antonio; Ralph Lorenz R. Apiladob; Joseph F. Bambico (Indonesian Journal of Agricultural Science, 2019)
A mutation in the rendement napole (RN) gene causes the acid meat condition which results to poor meat quality due to its reduced water holding capacity, low pH, pale color, reduced processing and cooking yield due to increased drip, and strong metallic taste. This study was conducted to detect the mutation in the RN gene in 535 commercial breeder pigs from the Philippines. Blood collection was done then subjected to DNA extraction and genotyping using polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP) using the enzyme BsrBI, then validated by DNA sequencing. Results revealed that 97.01% of the breeder pigs did not have the mutation in their RN gene, while 2.69% had at least one copy of the defective allele in their gene. The acid meat condition has only been previously detected in the Hampshire breed whereas this study found the mutations predominantly in Pietrain and Landrace breed they were classified as normal (rn/rn), heterozygous mutants (RN/rn), and homozygous mutants (RN/RN) which allowed breeding systems to be developed ensuring that all offspring are free of the defect.  This genetic screening will help in detecting the presence of the defect in a given swine population and reduce the unwanted effects on meat quality thus increasing its market value.